2020
DOI: 10.1039/c9se01288e
|View full text |Cite|
|
Sign up to set email alerts
|

Gradient formation and charge carrier dynamics of CuBiI4based perovskite-like solar cells

Abstract: The formation of a Bi gradient with a Bi/Cu bilayer as the precursor can improve the photoinduced charge carrier transportation in CuBiI4 films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Further, spark plasma sintering (SPS) was performed to make a high-density pellet for thermal conductivity measurement. It should be mentioned here that previously CuBiI 4 thin films were synthesized for solar cell-based applications. , The powder X-ray diffraction (PXRD) pattern of polycrystalline CuBiI 4 is well matched with the cubic Fd m crystal system, as shown in Figure b. The obtained lattice parameter from Rietveld refinement is 12.056 Å (Figure S2, Table S1, SI).…”
Section: Resultsmentioning
confidence: 99%
“…Further, spark plasma sintering (SPS) was performed to make a high-density pellet for thermal conductivity measurement. It should be mentioned here that previously CuBiI 4 thin films were synthesized for solar cell-based applications. , The powder X-ray diffraction (PXRD) pattern of polycrystalline CuBiI 4 is well matched with the cubic Fd m crystal system, as shown in Figure b. The obtained lattice parameter from Rietveld refinement is 12.056 Å (Figure S2, Table S1, SI).…”
Section: Resultsmentioning
confidence: 99%
“…As for the CuBiI 4 with defectspinel-type cubic structure, [81] Zheng and co-workers employed a highly facile method to in situ fabricate CuBiI 4 with a favorable bandgap of 1.81 eV. [82] In 2005, Oldag et al prepared the AgBiI 4 and Ag 3 BiI 6 via solvothermal method from nonstoichiometric mixtures of AgI and BiI 3 . [83] The prepared AgBiI 4 crystallizes in space group Fd3 m with edge-sharing bismuth and silver octahedral, while the Ag 3 BiI 6 crystallizes in space group R3 m. For the AgBi 2 I 7 , Sargent and co-workers reported that it crystallized in a cubic Fd3 m phase with a lattice parameter of 12.223 Å.…”
Section: A 2 Bbix 6 Double Perovskitesmentioning
confidence: 99%
“…In turn, polycrystalline thin films of these materials have been fabricated using various deposition strategies, such as spin-coating, [66,68] direct metal surface elemental reaction (DMSER), [101,102] and coevaporation. [71,103] In regard to optoelectronic devices, the material and film qualities are critical, as they affect the series and shunt resistances, carrier generation and extraction, recombination processes, and photon detection sensitivity. While phase-pure crystal growth commonly requires synthesis optimization or modification to attain a critical saturation point and nucleation, the film quality and coverage can be improved by accessing reliable and scalable solution-or vapor-based thin-film formation strategies.…”
Section: Synthesis and Thin-film Depositionmentioning
confidence: 99%
“…Moreover, CuBiI 4 is a promising candidate for tandem solar cells due to its suitable bandgap (1.8 eV) and photoelectric properties comparable to those of lead-based perovskites. [66,101,103] However, further modification of the synthesis process is required to improve the film morphology and its optoelectronic properties. Cu 3 SbI 6 , which has an indirect bandgap of ≈2.4 eV, has also been investigated as a photoactive material in solar cells.…”
Section: Cu X B Y I X+3y (B = Bi 3+ or Sb 3+ )mentioning
confidence: 99%
See 1 more Smart Citation